Stories That Make History Mexico through Elena Poniatowska's Crónicas - Stephen, Lynn (Duke University Press, 2021)
Lynn Stephen examines the writing of Elena Poniatowska, showing how it shaped Mexican political discourse and provides a unique way of understanding contemporary Mexican history, politics, and culture.